2020
DOI: 10.1186/s12865-020-0341-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive staining of the immunoligand B7-H6 in abnormal/transformed keratinocytes consistently accompanies the progression of cervical cancer

Abstract: Background: B7-H6 has been revealed as an endogenous immunoligand expressed in a variety of tumors, but not expressed in healthy tissues. Heretofore, no studies have been reported describing B7-H6 in women with cervical cancer. To investigate this question, our present study was conducted. Results: This retrospective study comprised a total of 62 paraffinized cervical biopsies, which were distributed in five groups: low-grade squamous intraepithelial lesions (LSIL), high-grade squamous intraepithelial lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…We showed that the surface expression of B7-H6 was present in around 50% of the cells in both cervical cancer cell lines, HeLa and SiHa. We are among the first to show the presence of B7-H6 in these cell lines, and these results are in line with a recent report by our group, where the expression of B7-H6 was consistently seen in cervical cancer specimens [ 20 ] As the expression of B7-H6 was not present in the totality of HeLa or SiHa cells, we tried to sort the B7-H6 positive and B7-H6 negative population and found that B7-H6 was selectively maintained or lost in the tumor cell lines. Both the positive and negative cell lines regained the expression with roughly the same percentage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We showed that the surface expression of B7-H6 was present in around 50% of the cells in both cervical cancer cell lines, HeLa and SiHa. We are among the first to show the presence of B7-H6 in these cell lines, and these results are in line with a recent report by our group, where the expression of B7-H6 was consistently seen in cervical cancer specimens [ 20 ] As the expression of B7-H6 was not present in the totality of HeLa or SiHa cells, we tried to sort the B7-H6 positive and B7-H6 negative population and found that B7-H6 was selectively maintained or lost in the tumor cell lines. Both the positive and negative cell lines regained the expression with roughly the same percentage.…”
Section: Discussionsupporting
confidence: 92%
“…The canonical role described for the B7-H6/NKp30 interaction is activation of the NK cell [ 16 , 17 ]. At a protein level, it has been found that B7-H6 is selectively expressed by a variety of malignant tumors, such as lymphoma, leukemia [ 10 ], gastric carcinoma [ 18 ], astrocytoma [ 19 ], cervical carcinoma [ 20 ] and is also expressed under inflammatory and stress conditions, but has not been seen in healthy cells [ 14 , 21 ]. Also, high amounts of B7-H6 mRNA have been found in ovarian cancer, brain tumors, breast cancer, and various sarcomas, while normal tissues under steady-state conditions apparently do not show detectable B7-H6 mRNA [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these signals, B7‐H6 /NKp30 pathway is involved in the NK cell‐mediated immune responses and tumor progression within a variety of tumors. Several previous studies demonstrated that the high expression of B7‐H6 was correlated with tumor progression and poor overall survival in some cancers (19–24, 27–29). Different research groups showed that B7‐H6 has no significant diagnostic or prognostic value in non‐small cell lung cancer and gastric cancer (26, 27).…”
Section: Discussionmentioning
confidence: 98%
“…B7‐H6 was also expressed in inflammatory monocytes, but not in healthy monocytes (18). Studies have reported that the expression of B7‐H6 is related to the metastasis of some cancers, and the B7‐H6 expression is negatively correlated with the overall survival (OS) rate of ovarian cancer, breast cancer, brain tumor, esophageal squamous cell carcinoma, cervical cancer, and esophageal squamous cell carcinoma (17, 19–24). However, the situation is not always the same, and it was found that the higher expression of B7‐H6 predicted favorable overall patient survival in gastric cancer (25).…”
mentioning
confidence: 99%
“…95 It has been reported that the expression of B7-H6 is positively correlated with disease stage in the development of cervical cancer, and the expression level is higher in cervical adenocarcinoma than that in SCC. 96 The studies on B7-H6 in gynecologic tumors are all in the preclinical stage, and there is no relevant clinical trial ongoing at present.…”
Section: B7-h6mentioning
confidence: 99%